(untitled) (Nigerian Journal of Technology, 2017)
This paper presents the conceptual design of plastic recycling machine for production of thin filament coil. The machine is meant to serve as a sustainable means of converting waste Polyethylene Terephthalate (PET) plastic materials into thin filaments to be used as feedstock material in Fused Deposition Modeling (FDM) machine. The machine design consists of a shredder hopper, two shredder shafts with knife-edge ring cutters, extruder hopper, extrusion barrel with heater jackets and extrusion auger shaft. The design analysis of each of the machine elements was done and structural integrity of the machine design was evaluated using finite element analysis (FEA) tool in Solid Works Computer Aided Design (CAD) application. The FEA result indicated that a maximum stress of 33 MPa was reached in one of the machine frame members when loads mounted on top and below the frame structure are 1204 N and 271 N respectively. The maximum resultant displacement in the member frame was 0.34 mm and the minimum factor of safety obtained was 8.3. Also, a minimum factor of safety value of 5.3 was obtained for shredder shaft between when subjected to a torque of 1000 Nm and it experienced an angle of twist of 0.42o and a maximum stress of 46.8 MPa. The implication of the result is that the design of the machine is adequate and the machine will fulfill its intended purpose upon fabrication, as the yield strengths of selected materials for the fabrication of the machine members are not exceeded. http://dx.doi.org/10.4314/njt.v36i2.13